Latest eco-friendly avenues on hydrogen production towards a circular bioeconomy: Currents challenges, innovative insights, and future perspectives. (October 2022) - Qureshi, Fazil; Yusuf, Mohammad; Kamyab, Hesam; Vo, Dai-Viet N.; Chelliapan, Shreeshivadasan; Joo, Sang-Woo; Vasseghian, Yasser
Abstract: The worldwide economic development, population expansion, and technological advancements contribute to a rise in global primary energy consumption. Since fossil fuels now provide around 85% of the energy requirement, a significant quantity of greenhouse gases is released, leading to climate change. To meet the pledges of the Paris agreement, a promising and potential alternative to fossil fuels needs to be commercialised. Therefore, numerous industries recognise hydrogen (H2 ) as a clean and stable energy source for decarbonisation or de-fossilisation. Around 90% of the world's H2 produced is grey in nature and produced from reforming fossil-based fuels. However, the future of H2 energy lies in its green, blue, and turquoise spectra due to the carbon capture scheme and corresponding clean and sustainable H2 production methodology. The fundamental goal of this research is to learn more about various low-carbon H2 generating systems. In comparison to fossil-based H2, green H2 is a costly option. Blue H2 offers several appealing characteristics; however, the carbon capture utilisation and storage (CCUS) technology are expensive and blue H2 is not carbon-free. The current CCUS technology can only store and catch between 80 and 95% of CO2 . Further, it examines worldwide actions related to the H2 development policy. In addition, a debate based on the colour spectrum of H2 was established to classify the purity of H2 generation. Further, the existing obstacles, advancements, and future directions of low-carbon H2 production technologies, including fossil fuel-based and renewable-based H2, are explored to foster the growth of the low-carbon H2 economy. Highlights: H2 is a promising alternative to fossil fuels that can aid to achieve pledges of Paris agreement. H2 production from steam reforming i.e., grey H2 is still the major production route. Future of H2 lies in blue, green, and turquoise spectrum, others will fade with time. Techno-economic feasibility needs further research for H2 production via electrolysis of H2 O.